Synergistic Effects of Nd Content and Cooling Rate on the Organization and Properties of Al-Nd Alloys - Wenjie Wu; Shuchen Sun; Xiangjie Wang; Xinyu Zhang; Chengcheng Chen; Xin Hong; Yaoyu Yan; Jing Wei; Ganfeng Tu (Crystals)
This research focuses on the synergistic effect of the cooling rate and solute neodymium (Nd) content on the microstructure and physical properties of aluminum-neodymium (Al-Nd) alloys. The results indicate that the cooling rate has a significant impact on the grain morphology, size, and morphology of eutectic Al₁₁Nd₃ in the alloy. As the cooling rate decreases, the grains transform from columnar crystals to equiaxed crystals, exhibiting different distribution characteristics in various regions, and the eutectic transforms from skeletal to lamellar and then to acicular. The Nd content affects the eutectic growth and solubility, reaching the maximum solubility at 11 wt.% Nd. Due to the longer diffusion time of Nd atoms in the slow-cooling region and the formation of compounds, the lattice constant in the slow-cooling region is larger. In terms of physical properties, the hardness and electrical conductivity of the alloy are inversely related. The hardness increases with an increases of the cooling rate and Nd content, which is attributed to grain refinement and solid solution strengthening, while the electrical conductivity decreases. These findings are of important theoretical and practical significance for optimizing the performance and application of Al-Nd alloys.